Abundance, distribution patterns, and identification of microplastics in Brisbane River sediments, Australia - He, Beibei; Goonetilleke, Ashantha; Ayoko, Godwin A.; Rintoul, Llew (The Science of the total environment, 2020)
[Display omitted] •Systematic investigations of microplastic pollutants in Brisbane River sediments.•Improved method of microplastic separation and extraction.•Distance-based distribution of microplastics hotspots occur in river sediments.•Weight is a realistic indicator for evaluating the extent of microplastic pollution. Plastic pollutants in aquatic ecosystems have received wide attention and research endeavours since early 1970s. However, in comparison to marine environments, the occurrence of microplastics in a tidal river system remains largely unknown, especially in river sediments. Sediment samples taken from twenty-two sampling points along Brisbane River over the four different seasons revealed relatively high concentrations of microplastics in river sediments, with abundance ranging from 0.18 to 129.20 mg kg−1, or 10 to 520 items kg−1. Unfortunately, varied methods and units used for reporting do not allow the accurate comparison between related studies. The spatial distributions of microplastics hotspots indicated that microplastics abundance is distance-dominated caused by flow velocities. Lower and higher concentrations of microplastics abundance mostly occurred in dry and wet seasons, respectively. Significant temporal variations of microplastics concentrations was observed in residential and commercial areas. Polyethylene (PE), polyamide (PA) and polypropylene (PP), were the three main polymer types found in the Brisbane River sediments. Other polymer types such as polyethylene terephthalate (PET) were also detected. The majority of the detected microplastic particles were found to be <3 mm. This study reveals the abundance, spatial and temporal distribution patterns, and characteristics of microplastic pollutants in Brisbane River sediments, and provides systematic data for further research on microplastics in estuarine environments worldwide.